The Moral Values of Children’s Storybooks Entitled Tom Sawyer, Little Woman and Robinson Crusoe to Develop Character Education to Elementary School Students - Habibullah, Naufal Luthfi Afif; Widiarti, Tri Rini (Forum Akademisi dan Dosen Peneliti (FAST), 2026)
Moral values are ones regarding teachings about good life behavior based on certain views of life or religion. Moral values are important to teach in order to build good character. This study aims to analyze the moral values conveyed in children's story books entitled Tom Sawyer, Little Woman, and Robinson Crusoe, to develop character education for elementary school students. This research uses a library research design. The procedure of this research such as reading, taking notes, data classification, and data analysis. As a result, there are three triangulations: triangulation of sources, triangulation of data collection methods, and triangulation of time. After that, the snippet of the story containing moral values was written by the researcher according to the title of the related book. The data found on tables based on story snippets and moral values with different tables for each book. The research finding showed that each story excerpt contains moral values. The moral values contained in the three storybooks include trust, honesty, hard work, prohibition of lying, dynamic, positive thinking, generosity, self-esteem, trustworthiness, patience, adaptability, religion, self-confidence, beneficial to others. Moral stories create opportunities for children to learn meaningful lessons as well as in achieving broader learning, where they can show compassion and empathy to one another and at the same time be part of a community, creating positive change.